Microbial Diversity and Composition in Six Different Gastrointestinal Sites among Participants Undergoing Upper Gastrointestinal Endoscopy in Henan, China - Minjuan Li; Dantong Shao; Jiachen Zhou; Jianhua Gu; Junjie Qin; Xinqing Li; Changqing Hao; Wenqiang Wei (Microbiology Spectrum, 2022)
ABSTRACT The objective of this study was to describe and compare the dynamic microbiota characteristics in the gastrointestinal (GI) tract in Chinese participants via high-throughput sequencing techniques. The study collected saliva, esophageal swab, cardia biopsy, noncardia biopsy, gastric juice, and fecal specimens from 40 participants who underwent upper GI tract cancer screening in Linzhou (Henan, China) in August 2019. The V4 region of 16S rRNA genes was amplified and sequenced using the Illumina MiniSeq platform. The observed amplicon sequence variants (ASVs) gradually decreased from saliva to esophageal swab, cardia biopsy, noncardia biopsy, and gastric juice specimens and then increased from gastric juice to fecal specimens (P < 0.05). Each GI site had its own microbial characteristics that overlapped those of adjacent sites. Characteristic genera for each site were as follows: Neisseria and Prevotella in saliva, Streptococcus and Haemophilus in the esophagus, Helicobacter in the noncardia, Pseudomonas in gastric juice, Faecalibacterium, Roseburia, and Blautia in feces, and Weissella in the cardia. Helicobacter pylori-positive participants had decreased observed ASVs (cardia, P < 0.01; noncardia, P < 0.001) and Shannon index values (cardia, P < 0.001; noncardia, P < 0.001) compared with H. pylori-negative participants both in cardia and noncardia specimens. H. pylori infection played a more important role in the microbial composition of noncardia than of cardia specimens. In gastric juice, the gastric pH and H. pylori infection had similar additive effects on the microbial diversity and composition. These results show that each GI site has its own microbial characteristics that overlap those of adjacent sites and that differences and commonalities between and within microbial compositions coexist, providing essential foundations for the continuing exploration of disease-associated microbiota. IMPORTANCE Upper gastrointestinal (UGI) tract cancer is one of the most common cancers worldwide, while limited attention has been paid to the UGI microbiota. Microbial biomarkers, such as Fusobacteria nucleatum and Helicobacter pylori, bring new ideas for early detection of UGI tract cancer, which may be a highly feasible method to reduce its disease burden. This study revealed that each gastrointestinal site had its own microbial characteristics that overlapped those of adjacent sites. There were significant differences between the microbial compositions of the UGI sites and feces. Helicobacter pylori played a more significant role in the microbial composition of the noncardia stomach than in that of the cardia. Gastric pH and Helicobacter pylori had similar additive effects on the microbial diversity of gastric juice. These findings played a key role in delineating the microbiology spectrum of the gastrointestinal tract and provided baseline information for future microbial exploration covering etiology, primary screening, treatment, outcome, and health care products.